The astrocytic sigma-1 receptor constitutes in the fast antidepressant action of hypidone hydrochloride (YL-0919) in rodents - Jin-Feng Li; Jin-Feng Li; Hai-Xia Chang; Jia-Ning Zhao; Jia-Ning Zhao; Jin-Hao Bao; Wei Dai; Yun-Feng Li; Yun-Feng Li (Frontiers in Pharmacology)
Introduction: There is increasing evidence that astrocytes are involved in the therapeutic action of antidepressants. The fast antidepressant YL-0919 may interact with activation of astrocytic sigma-1 receptors (sigma-1R).Methods: In this study, function of astrocytic sigma-1R in ventral hippocampus (vHIP) mediating the rapid antidepressant effect of YL-0919 were investigated. Adeno-associated virus (AAV) expressing shRNA was constructed to knock down astrocytic sigma-1R in vHIP, and the role of astrocytic sigma-1R on the rapid antidepressant action of YL-0919 were tested in chronic restraint stress (CRS) model of mice. Small interfering RNA (siRNA) was used to knock down sigma-1R in primary astrocytes, and we explored the mitochondrial function and BDNF expression of primary astrocytes after YL-0919 and siRNA treatments. Result: The results indicated knocking down astrocytic sigma-1R in vHIP induced anxiety-like and depressive-like behavior in mice, and blocked the rapid anti-depressant and anxiolytic effects of YL-0919. Knocking down sigma-1R in primary astrocytes inhibited the YL-0919 induced enhancement of mitochondrial function and increased level of BDNF expression. In addition, increased BDNF in vHIP might play a role in fast antidepressant impact of YL-0919. Taken together, the data provide further evidence for a role of astrocyte receptors in the mechanisms of action of antidepressants.Conclusion: Taken together, these results reveal increased BDNF in vHIP by affecting glial cells might be one of the significant mechanisms of fast antidepressant effect of YL-0919. The data provide further evidence for a role of astrocyte receptors in the mechanisms of action of antidepressants.